Temperature induced high charge–discharge performances in lead-free Bi0.5Na0.5TiO3-based ergodic relaxor ferroelectric ceramics. (December 2017) - Li, Feng; Yang, Ke; Liu, Xing; Zou, Jian; Zhai, Jiwei; Shen, Bo; Li, Peng; Shen, Jie; Liu, Baihui; Chen, Pan; Zhao, Kunyu; Zeng, Huarong
Abstract: The temperature dependence of energy storage and charge–discharge properties of a lead–free 0.62Bi0.5 Na0.5 TiO3 –0.06BaTiO3 –0.32(Sr0.7 Bi0.2 □0.1 )TiO3 ergodic relaxor ferroelectric ceramic were investigated. The energy storage density was maintained ≥ 0.5 J/cm 3 up to 140 °C with a high efficiency ≥ 90%. The stored energy was released in sub–microsecond durations and charge–discharge performances were enhanced as temperature increased to 160 °C. This ceramic possessed an enhanced power density 18.2 MW/cm 3 and large current density 606 A/cm 2 . All results showed that this ergodic relaxor ferroelectric ceramics appeared very promising for pulse capacitor applications. Graphical abstract: